The questions asked by the islamic fundamentalism and the principles of planetary citizenship - Borgia, Guglielmo (Formazione & insegnamento, 2017)
The first part of this new millennium presents us a political and economic context in which the so-called globalized society is rising from the ranks setting as its first foundation the constitution of planetary citizenship, considered the first principle for the affirmation of human rights and of civil co-habitation, in order to realise pacification, solidarity and equality among peoples. Unfortunately this rising “Global Village” is still continuously tormented by so many conflicts, destructiveness, inequalities and injustices. Among peoples a climate of generalised violence and creeping terror prevails, causing in the “citizens” of the planet bewilderment, distrust, insecurity and anxiety. Therefore, the planetary citizenship is continually threatened by a strong competitiveness and individualism making human beings threatening and threatened, it follows that many layers of the world population do not feel ensured their fundamental rights. In such a direction, the educational action can represent the keystone that works as a critical force of emancipation of consciences and avoids the flattening on ideological positions that undermine at the base the ongoing process of promotion of civil co-habitation, safeguard of human rights and the constitution of a planetary citizenship as guarantee of global peace and fundamental rights of the human being.